Inclusione, una comprensione profonda. Gli atteggiamenti inclusivi degli insegnanti tra valori e pratica - Camedda, Donatella (My University, 2016)
The effort to foster inclusive education in schools as a community endeavour, which involves the growth of connections based on the valuing of diversity, contrasts sharply with the current tendency to assess academic success in terms of individual performance. The ranking systems increasingly adopted worldwide to reinforce pupil stratification according to school attainment tend to reduce students to the bearers of results, dramatically impoverishing the complexity and wealth of educational experience (Slee, 2011). Thus, the urge to promote the active engagement of community stakeholders in creating more diverse and dynamic schools implies a claim to achieving more equity and social justice in educational settings. However, such an involvement is not just the consequence of assuming an ethical, value-based perspective of what education is supposed to be today, but also reflects the current evolution of school organization (Apple, 2014; Ball, 2010a; Ballantine, Hammack, 2012; Young, Muller, 2016).
None excluded. Transforming schools and learning to develop inclusive education
Nessuno escluso. Trasformare la scuola e l’apprendimento per realizzare l’educazione inclusiva
Keywords: Inclusive Society; Disability Inclusion; EDUCATION; Other; Attitudes